SUMO-interacting motifs (SIMs) in Polo-like kinase 1-interacting checkpoint helicase (PICH) ensure proper chromosome segregation during mitosis. Issue 16 (17th August 2016) - Sridharan, Vinidhra; Azuma, Yoshiaki
ABSTRACT: Polo-like kinase 1 (Plk1)-interacting checkpoint helicase (PICH) localizes at the centromere and is critical for proper chromosome segregation during mitosis. However, the precise molecular mechanism of PICH's centromeric localization and function at the centromere is not yet fully understood. Recently, using Xenopus egg extract assays, we showed that PICH is a promiscuous SUMO binding protein. To further determine the molecular consequence of PICH/SUMO interaction on PICH function, we identified 3 SUMO-interacting motifs (SIMs) on PICH and generated a SIM-deficient PICH mutant. Using the conditional expression of PICH in cells, we found distinct roles of PICH SIMs during mitosis. Although all SIMs are dispensable for PICH's localization on ultrafine anaphase DNA bridges, only SIM3 (third SIM, close to the C-terminus end of PICH) is critical for its centromeric localization. Intriguingly, the other 2 SIMs function in chromatin bridge prevention. With these results, we propose a novel SUMO-dependent regulation of PICH's function on mitotic centromeres.